Innovative Path of the Regional Economy’s Departure from the Previous Path-Dependent Development Trajectory - Rastvortseva, Svetlana Nikolaeva (Economy of Regions, 2020)
The diversification of regions in terms of economic growth rate is largely due to the path dependence: a region's economy depends on the earlier established industrial structure. Successfid regions, formed as an economic “core”, now have more reasons for creating a new economy and ensuring further economic growth. Existing institutions and norms, returns to scale, inertial development are the constraining factors for the path-breaking. The paper shows that the departure from path dependency for the regions is possible through technological innovations and interregional relations. The study aims to develop a method for assessing a region’s path-breaking possibility based on the existing industrial structure and its connection with the economy’s hightech sector. The proposed assessment method is based on using the localization coefficient for determining the proximity of types of economic activity (that have a comparative advantage in a region) with the economy’s high-tech sub-sectors. The approach has been tested in the regions of Russia. We have shown that certain regions can move further by investing in interregional ties and internal innovations. These two factors contribute to the rapid development, reduce dependence on the established industrial structure, allow maintaining comparative advantages. The research has practical significance as it offers an analytical tool for making decisions about the possibility and directions of a regions path-breaking. It is important to understand in which direction a region shoidd develop inter-sectoral cooperation for the emergence of the economy’s new sectors.